Avaliação do potencial de geração de biogás a partir de resíduos orgânicos de um restaurante popular - Rocha, Mayesk Alves (2022)
The urgency of innovation in the energy field, combined with environmental concerns andthehigh generation of waste on the world stage, increasingly encourages the use of anaerobicdigestion techniques as a prosperous technology for the treatment of such environmentalliabilities and biogas production. In this way, the use of a digester to produce biogas is oneofthe possible ways to take advantage of the renewable energy potential availableintheenvironment. Therefore, the research aimed to evaluate the potential of biogas productioninthe operation of a batch bench biodigester, from waste produced in a popular restaurantlocated in the neighborhood of Rosa Elze, in the city of São Cristóvão, using goat manureasinoculum, in concentrations (0, 1, 2 and 3%). The biodigesters used in the studyweredeveloped from the reuse of polyethylene terephthalate (PET) bottles and operatedfor 21daysat a temperature of 25 °C. It was possible to verify the evolution of the daily generationofbiogas through the anaerobic decomposition of organic matter and, also, to monitor thetemperature and pH of the samples, in addition to performing the analyzes of nitrogen,phosphorus, Chemical Oxygen Demand (COD) and total, volatile and fixed solids. Accordingto the results found in this research, the best condition for the production of biogas wasat aconcentration of 3% of inoculum, with a pH of 7.12, that is, with pH adjustment, obtainingaproduction of 18 mL of biogas. In relation to volatile and fixed solids, concentrationsof25.9% and 1.3% were reached, respectively. As for the COD, nitrogen and phosphorusanalyses, there was a reduction of 44%, 72.2% and 84%, in that order. In terms of energygeneration potential, the present work obtained a generation of 321 kWh/month and, usingthetariff calculations presented on the portal of the energy company operating in theStateofSergipe, ENERGISA, it was possible to acquire as a value charged to the groupthat therestaurant is included, a value of R$ 0.49 per kWh consumed in the green tariff, indicatingagain of R$ 157.97/month with the biogas produced by food waste fromthe popular restaurant.The results show the promising use of organic waste from the restaurant as a source for biogasformation and energy generation. They also indicated anaerobic digestion as a sustainableprocess and the benchtop biodigester a great option for gas production, being efficient andlow cost.